Penerapan Metode An-Nahdliyah dalam Meningkatkan Hasil Belajar Al-Qur’an Peserta Didik di Madrasah Ibtidaiyah - Iskandar, Hamim; Khaer, Misbakhul (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to analyze the application of the An-Nahdliyah method in improving the learning outcomes of students in Islamic Elementary Schools (MI). The research method used is qualitative descriptive analytic with research subjects including ustadz, ustadzah, students, and madrasah principals in three MI in East Java. Data were collected through participatory observation, in-depth interviews, and documentation studies for six months. The results showed that the An-Nahdliyah method effectively improves students’ ability to read the Quran with an increase in accuracy of makharijul huruf by 85%, ability to read tartil by 78%, and reading speed by 40% without reducing the quality of reading. Supporting factors for success include adequate teacher competence, conducive learning infrastructure, and support from parents and the community. Student responses showed high enthusiasm with a motivation level of 92%, which contributed to increased self-confidence and interest in learning the Quran. Challenges faced include the heterogeneity of students’ initial abilities and limited learning time. This research provides an important contribution to the development of more effective Qur’an learning methods that are appropriate to the context of Islamic education in Indonesia.